IMPLEMENTASI DATA MINING MENGGUNAKAN ALGORITMA APRIORI UNTUK ANALISIS POLA PEMBELIAN MENU PADA KAFE TOKOPI LEIPE - Elismawati, Elismawati; Agarina, Mleda (LP2M Institut Informatika Dan Bisnis Darmajaya, 2025)
The rapid growth of cafes has led to an increase in transaction data that is often underutilized. This study aims toimplement data mining using the Apriori algorithm to analyze menu purchasing patterns at TOKOPI LEIPE Cafe. Thedata used are real transaction data collected over a three-month period and anonymized to protect privacy. The researchmethod follows the Knowledge Discovery in Database (KDD) stages, including data collection, data cleaning, datatransformation, modeling, and evaluation. The results show association rules that describe combinations of menusfrequently purchased together based on support and confidence values. These findings are expected to assist cafemanagement in developing menu bundling strategies, promotions, and inventory planning